Against the background of social reality
1 online resource
Keywords: "The first wide-ranging, organic analysis of the sociology of unmarkedness and taken-for-grantedness, this volume investigates the asymmetry between how we attend to the culturally emphasized features of social reality and ignore the culturally unmarked ones"--